Concentric Needle Electromyography Findings in Patients with Ulnar Neuropathy at the Elbow - Simon Podnar (NeuroSci)
In ulnar neuropathy at the elbow (UNE), the degree of neuropathic changes, the sensitivity of needle electromyography (EMG) in individual ulnar muscles, and the utility of individual EMG parameters are controversial. I compared qualitative needle EMG findings in two ulnar-innervated hands muscles and two ulnar-innervated forearm muscles in a group of previously reported UNE patients. Altogether, 170 UNE patients (175 arms) were studied. I found spontaneous denervation activity (SDA) most frequently in the first dorsal interosseus (FDI) (62%) and neuropathic changes in the abductor digiti minimi (ADM) muscle (88%). In the forearm muscles, SDA was more common (29% vs. 20%; p = 0.02), and neuropathic changes were similar in the flexor carpi ulnaris (FCU) and the flexor digitorum profundus (FDP) muscles. SDA and neuropathic changes were more common in the ulnar hand (88% and 77%) than in the ulnar forearm muscles (71% and 68%). Needle EMG is sensitive to diagnose UNE. For the detection of SDA FDI and neuropathic changes, ADM is the best muscle. Ulnar forearm muscles are less useful than ulnar hand muscles for UNE diagnosis.